Lactobacillus catenaformis associated lung empyema - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; How, Soon Hin; Ibrahim, Aishah; Baharudin, Roesnita (2019)
Introduction Lactobacillus catenaformis is a gram positive, anaerobic, non-motile and non-spore forming rod belonging to the Erysipelostrichaceae family. This bacterium was reclassified as Eggerthia catenaformis in 2011 after phylogenetic analysis of its genome. It has been proven that this strain can be a human pathogen and can carry genes related to virulence. Here we describe the clinical case of a patient with a lung empyema caused by Lactobacillus catenaformis.